Battery durability and reliability under electric utility grid operations: Representative usage aging and calendar aging. (August 2018) - Dubarry, Matthieu; Devie, Arnaud
Graphical abstract: Highlights: BESS representative battery usage as well as aggressive/mellow usage tested under controlled conditions. Up to 4000 cycles at 3C on commercial LTO based Li-ion cells. Capacity loss found to increase with temperature and current, opposite for SOC swing. No major combined effect indentified. Abstract: Battery energy storage systems (BESS) are often viewed as solution to mitigate the intermittency of renewable energies in electric grids. However, battery degradation associated with grid-tied BESS usage has never been investigated in detail. This work was aimed at understanding the impact of a BESS representative usage profile on the degradation of commercial Li-ion cells. It was found that the cell temperature history had the strongest impact on battery degradation followed by the C-rate and the state of charge (SOC). Also, batteries lost capacity faster at low SOCs during calendar aging and under small SOC swings while cycling.